Does the alternative respiratory pathway offer protection against the adverse effects resulting from climate change? - Florez-Sarasa, Igor (Journal of experimental botany, 2020)
© The Author(s) 2019. Published by Oxford University Press on behalf of the Society for Experimental Biology.